(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Justice collaborators are exposed to the highest risk of retaliation, as they have decided to testify against their former associates (members and leaders of criminal organizations) through cooperation with prosecution authorities in order to gain certain privileges. In one person, the justice collaborator, two procedural features are merged: the collaborator’s during the conclusion of the agreement, and the witness’, after the agreement was accepted by the court and his testimony given. After the testimony was given and the criminal proceeding was completed, these persons are not unattended, but every state that faces threats of organized forms of criminal activity is obliged to provide them both procedural and non-procedural (Program) protection. This paper presents the procedure of providing program protection to justice collaborators in the legislations of the Republic of Serbia, the Republic of North Macedonia, the United States of America, England and Italy, the extent of its efficient implementation and the real and potential difficulties in front of persons included in the Program.